Dynamics Of Asean, US, and China Capital Market Relations: Before, During and Post Covid-19 - Hariani, Swarmilah; Halim, Abdul; Hendryadi, Hendryadi; Budiharjo, Roy; Malik, Hafiz Abdul Samee (Universitas Muhammadiyah Malang, 2024)
Purpose: The study aims to uncover the dynamics of the relationship between ASEAN countries (Malaysia, Singapore, Thailand, and the Philippines), the US, and China to the Indonesian capital market. Methodology/approach: This study uses weekly composite stock price index data for two observation periods: January 2016 to December 2019 (pre-COVID-19) and January 2020 to December 2023 (during and post-COVID-19). The econometric model is analyzed separately for (i) Indonesia and other ASEAN markets, and (ii) Indonesia, the US, and China. Findings: The ARDL cointegration analysis reveals that before COVID-19, the Indonesian stock market was influenced by Malaysia, the Philippines, and Thailand within the ASEAN data group, while only China had a long-term impact within the Indonesia-US-China data group. In the short term, there was a stronger link between the Indonesian capital market and Malaysia compared to Singapore, the Philippines, and Thailand. After the pandemic, there was a significant increase in the relationship between China's capital market and Indonesia, while the impact of the U.S. stock exchange on Indonesia was considered insignificant in the short term. Practical implications: This study can help investors and policymakers make informed decisions regarding portfolio diversification and risk management. More importantly, the long-term impact of China on the Indonesian stock market; so investors in Indonesia need to monitor and assess developments in the Chinese market for potential long-term implications. Originality/value: This study offers new insights into the dynamics of the relationship between the Indonesian capital market and ASEAN, the US, and China; a topic that has been relatively under-researched in the context before and after the COVID-19 pandemic.